A vivência de familiares cuidadores de crianças acometidas por fibrose cística à luz da teoria de callista roy - MARCELINO, Thais Cristina Flexa Souza (Universidade Federal do Pará, 2023)
Within the family there are several healthillness situations that can occur, among them the diagnosis of a chronic illness in a child, such as cystic fibrosis, causing a disorder that has a biological, psychological and cognitive basis. Cystic Fibrosis or Mucoviscidosis is a serious genetic and hereditary disease and particularly affects the lungs and pancreas. The aim of the study was to know the experiences of family caregivers of children with cystic fibrosis in the light of Callista Roy's Theory of Adaptation and to propose nursing interventions to family caregivers of children with cystic fibrosis. The study was performed at the João de Barreto Hospital Unit in the Cystic Fibrosis Outpatient Clinic. Fifteen family caregivers aged 2363 years participated in the study. During the evaluation of stimuli, the focal stimulus is full of stress, by organizing a new work and domestic routine and observing religious practices for the relief of suffering. As for the contextual stimuli, the social life is affected and there is an increase of the domestic tasks due to the disease, the attention turns completely to the child. Regarding residual stimuli, it was noted that the fear of losing the child is constant. After the evaluation of the behavior, it is inferred that the most affected part is emotional, dysfunctions occurred in the physiological way like increase of the blood pressure, obesity and overweight, insomnia and sudden weight loss. The way of selfconcept is harmed, they always prioritize children instead of themselves. In the role of paper, the point of support is the nuclear family, in which they share and deal with emotional and financial problems. Feeling of sadness, anger and worry are often observed in the mode of interdependence. Therefore, this study in the vision of the Adaptive Theory of Callista Roy fit ideally for the analysis of the experience of the familiar caregiver to the child with cystic fibrosis. Following the course of the theory, one can visualize the stimuli received from the environment and how these influence the generated behavior.